PENGARUH MEDIA TINY TASK BOX TERHADAP MOTORIK HALUS ANAK DI TAMAN KANAK-KANAK YAYASAN AMALAN KOTA PADANG - Refni Septianti; Indra Yeni; Farida Mayar; Setiyo Utoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Tiny Task Box media on the fine motor skills of children at the Yayasan Amalan Kindergarten in Padang City. The study is motivated by the suboptimal development of children's fine motor skills. Based on preliminary observations, children struggled with holding pencils properly, organizing and pasting neatly, buttoning shirts during life skills activities, and tying shoelaces. This study employed a quantitative method with a quasi-experimental design. The population consisted of 30 children from the Yayasan Amalan Kindergarten, with a sample size of 20 children divided into two groups: an experimental class and a control class. Data were collected through observation, tests, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and an independent sample t-test via SPSS 29, with a significance level of 5% (α = 0.05). The results indicated that the average score increase in the experimental class using the Tiny Task Box media was higher than that of the control class. The experimental class average score rose from 11.1 (pre-test) to 17.8 (post-test), while the control class rose from 11.8 (pre-test) to 16.0 (post-test). The hypothesis testing yielded a Sig. (2-tailed) value of 0.043, which is less than 0.05 (0.043 < 0.05). Consequently, it can be concluded that the Tiny Task Box media has a significant effect on improving children's fine motor skills at the Yayasan Amalan Kindergarten in Padang City.